Efectos de un taller basado en la pedagogía del amor y la ternura para mejorar la disciplina en estudiantes de primer grado de primaria de una escuela arequipeña - Sánchez Sanssoni, Mónica del Carmen (2019)
In the present study is based on the pedagogy of love and tenderness and the reality that you live in the classrooms of the primary level in reference to school discipline. Therefore a sample of 21 boys and girls has been selected to demonstrate that the application of the workshop "Dreams of love", based on the pedagogy of love and tenderness improves school discipline in primary education students. The results show the experience that was to apply the workshop and the significant results in reference to school discipline before and after the implementation of the workshop.